If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -7y = -9 Solving 5x + -7y = -9 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7y' to each side of the equation. 5x + -7y + 7y = -9 + 7y Combine like terms: -7y + 7y = 0 5x + 0 = -9 + 7y 5x = -9 + 7y Divide each side by '5'. x = -1.8 + 1.4y Simplifying x = -1.8 + 1.4y
| 3x-16= | | -107x-7x=7x+19 | | 24x^2-47+20=0 | | x^2-7s=0 | | x^20-7s=0 | | (x-18)(x^2-36)=0 | | -6x^3-10x^2-6x=0 | | factorx^4+16= | | 12-4*(8-x)=20 | | x^4+16= | | 1/u+6=-6 | | -3(2s-3)-9=-2(7s+7)-2 | | x*y=1512 | | 10x-4x= | | 6timesx=4 | | 5(x-7)=40 | | 5z-10z=45 | | y=-3/5x+b | | -1xy+2x^2+-6y^2= | | 6x^2-3xy-18y^2= | | (2/x-7)=3 | | (11b-4)-5(2b+1)=-5 | | 2x^7+2x^6-4x^5= | | (9x-9/7)+(8-x/3)=9 | | 9x+5x+3+8=11x+4+2x | | 33*w=52 | | (6x^2+22+17)/(x+3) | | w*2w-5=52 | | 2w^2-5w-17-w^2+2w-1=0 | | 2w^2-5w-17-w^2+2w-1=00 | | 2u^2-24u+70-u^2+14u-49=0 | | 2w^2-3w-16-w^2+4w-4=0 |